Perbaikan Kualitas Produk Kaos Sablon Berdasarkan Area Kerja Menggunakan New Seven Tools Dan 5S - Hirawati Oemar; Widya Widianti; Dewi Shofi Mulyati (JIE Scientific Journal on Research and Application of Industrial System, 2020)
CV. Bandung Mulia Konveksi is one of the clothing convection company located in Bandung which produces three types of products includes jackets, screen printing t-shirts and shirts. The products are produced by passing the same workstation namely the workstation of pattern, cutting, screen printing, and sewing. Based on data on the amount of production and data on the number of defective products in the last five years, CV. Bandung Mulia Konveksi can be seen that only screen printing t-shirts that have a percentage of disability outside the company's tolerance limit. Defects that occur on screen printing t-shirts can be known based on the work area. Quality improvement can be done using New Seven Tools to identify problems and 5S concepts for proposed improvements. The 5S checklist audit results and the giving of the 5S score on the conditions prior to the 5s applications a score of 20% is obtained, which means it is very bad. Whereas after the 5S implementation and the 5S audit checklist were carried out and the 5S score was given, the score increased to 62% which means good.